PENGARUH KEPEMILIKAN MANAJERIAL DAN PROFITABILITAS TERHADAP INTEGRITAS LAPORAN KEUANGAN PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sitti Muliana; Nur Rayhan Try Ramadhani; Nur Fatwa Basar; Nur Aisyah; Nurlaila Hasmi (Komunitas Manajemen Kompetitif, 2026)
The purpose of this study is to determine the effect of managerial ownership and profitability on the integrity of financial statements in LQ 45 companies listed on the Indonesia Stock Exchange. The data used in this study is quantitative. The data source used in this study is secondary data, with the analysis method using multiple linear regression. The results of this study indicate that managerial ownership and profitability have a positive and significant effect on the integrity of financial statements, as higher managerial ownership and profitability will improve the integrity of a company's financial statements.